Reading texts : reading, responding, writing - McCormick, Kathleen; Waller, Gary.; Flower, Linda (Lexington, MA : D.C. Heath, 1987)
This book is divided into three parts: Understanding the Reading Situation, incorporates the central insights of recent reader-cenntered and culturally focused criticism; Understanding the Writing Situation with the goals and strategies of process-oriented; and Reading, Responding, Writing...
Keywords: English language; Rhetoric; Report writing; College readers; English language -- Rhetoric -- Problems, exercises, etc; Report writing -- Problems, exercises, etc; College readers